Defining "Literature" (DETLI) - Garrido Gallardo, Miguel Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The DETLI aims at contributing to the Spanish language with a updated information of literary and cultural terms included in important encyclopedias created by the cultural base of the main languages of the Western World. In the era post literary, door of the twenty-first century, the cultural compartments that each of these languages involve represent a very important incentive. For example: LITERATURE.